Purification and synergistic antibacterial activity of arginine derived cyclic dipeptides, from Achromobacter sp. associated with a rhabditid entomopathogenic nematode against major clinically relevant biofilm forming wound bacteria - S, NISHANTH K. (Frontiers in Microbiology, 2015)
Skin and chronic wound infections caused by various pathogenic bacteria are an increasing and urgent health problem worldwide. In the present study ethyl acetate cell-free culture filtrate of an Achromobacter sp. associated with a Rhabditis entomopathogenic nematode (EPN), displayed promising antibacterial property and was further purified by silica gel column chromatography to get three different cyclic dipeptides (CDPs). Based on the spectral data and Marfey’s analyses, the CDPs were identified as cyclo(D-Leu-D-Arg) (1), cyclo(L-Trp-L-Arg) (2), and cyclo(D-Trp-D-Arg) (3), respectively. Three CDPs were active against all the ten wound associated bacteria tested. The significant antibacterial activity was recorded by CDP 3, and highest activity of 0.5 µg/ml was recorded against Staphylococcus aureus and Pseudomonas aeruginosa. The synergistic antibacterial activities of CDPs and ampicillin were assessed using the checkerboard microdilution method. The results of the current study recorded that the combined effects of CDPs and ampicillin principally recorded synergistic activity. Interestingly, the combination of CDPs and ampicillin also recorded enhanced inhibited biofilm formation by bacteria. Moreover, CDPs significantly stimulate the production of the anti-inflammatory cytokines IL-10 and IL-4 by human peripheral blood mononuclear cells but are without significant effect on the production of TNF-α, a pro-inflammatory cytokines. The three CDPs have been examined for their activities against intracellular S. aureus in murine macrophages (J774) using 24 h exposure to 1X and 2X MIC concentrations. Significance decrease in intracellular S. aureus burden was recorded by CDPs. CDPs also recorded no cytotoxicity towards FS normal fibroblast, VERO and L231 normal lung epithelial cell lines. Antimicrobial activity of the arginine containing CDPs against the wound associated bacteria is reported here for the first. Moreover, this is also the report on the production of CDPs